The ARL2 GTPase regulates mitochondrial fusion from the intermembrane space. Issue 3 (3rd July 2017) - Newman, Laura E.; Schiavon, Cara R.; Turn, Rachel E.; Kahn, Richard A.
ABSTRACT: Mitochondria are essential, dynamic organelles that regularly undergo both fusion and fission in response to cellular conditions, though mechanisms of the regulation of their dynamics are incompletely understood. We provide evidence that increased activity of the small GTPase ARL2 is strongly correlated with an increase in fusion, while loss of ARL2 activity results in a decreased rate of mitochondrial fusion. Strikingly, expression of activated ARL2 can partially restore the loss of fusion resulting from deletion of either mitofusin 1 (MFN1) or mitofusin 2 (MFN2), but not deletion of both. We only observe the full effects of ARL2 on mitochondrial fusion when it is present in the intermembrane space (IMS), as constructs driven to the matrix or prevented from entering mitochondria are essentially inactive in promoting fusion. Thus, ARL2 is the first regulatory (small) GTPase shown to act inside mitochondria or in the fusion pathway. Finally, using high-resolution, structured illumination microscopy (SIM), we find that ARL2 and mitofusin immunoreactivities present as punctate staining along mitochondria that share a spatial convergence in fluorescence signals. Thus, we propose that ARL2 plays a regulatory role in mitochondrial fusion, acting from the IMS and requiring at least one of the mitofusins in their canonical role in fusion of the outer membranes.